Technological parks as a mechanism for the implementation of innovation policy of the state - Maltseva, S.V.; Piddubna, O.A.; Khomenko, Ya.V. (Економічний вісник Донбасу, 2010)
The article presents the concept of technopark, his primary purposes and tasks. The indicators of technopark’s activity in Ukraine are analyzed. Urgency of creation of technological parks for maintenance of a sustainable development of economy of Ukraine is proved. Key words: technological park, innovation activity, investments, investor, high technological production, export potential. У статті розглянуто поняття технопарку, його основні цілі та задачі. Проаналізовані показники діяльності технопарків в Україні. Обґрунтована актуальність створення технологічних парків для забезпечення стійкого розвитку економіки України. Ключові слова: технологічний парк, інноваційна діяльність, інвестиції, інвестор, високотехнологічна продукція, експортніи потенціал. В статье рассмотрено понятие технопарка, его основные цели и задачи. Проанализированы показатели деятельности технопарков в Украине. Обоснована актуальность создания технологических парков для обеспечения устойчивого развития экономики Украины. Ключевые слова: технологический парк, инновационная деятельность, инвестиции, инвестор, высокотехнологическая продукция, экспортный потенциал.